Efektivitas Mediasi Dalam Perkara Perceraian Gugat di Pengadilan Agama Surabaya - Qotrunnada, Eliza; Fikri, Abdullah (Hukum dan Masyarakat Madani, 2025)
This study aims to evaluate the effectiveness of mediation in divorce cases at the Surabaya Religious Court during the period from 2020 to 2023. The research method used is a juridical- empirical approach with a legislative approach, which combines legal analysis with empirical observation of practices in the field. The study utilizes various legal materials, including primary legal materials such as relevant laws and regulations, secondary legal materials such as journals and legal literature, as well as relevant non-legal materials. The research results indicate that although the mediation process in divorce cases at the Surabaya Religious Court has been implemented according to established procedures, its effectiveness is still far from satisfactory. Several factors contribute to this ineffectiveness, including societal culture and the implications of the feminist movement, which have raised women's awareness of their rights. This awareness has led women to take on dual roles within the household, fostering the belief that independent women do not need husbands to survive and meet their children's needs. The study concludes that to improve the effectiveness of mediation in divorce cases, further efforts are needed, such as strengthening divorce prevention in the pre-marital process by enhancing education or counseling for couples and reinforcing family resilience by facilitating access to marriage and family counseling services. Additionally, the government needs to evaluate the performance of external factors affecting society and revise the mediation regulations currently in force in the courts. Keywords : Mediation, Effectiveness, Divorce, Religious Court